Structural features of chromium carbide coatings obtained by the MOCVD method from the COL "BARKHOS" - Krokhmal, S.A.; Kazarinov, Yu.G.; Zueva, T.N. (Вопросы атомной науки и техники, 2021)
Investigations of the structure and properties of gas-phase coatings obtained with the use of chromium organic liquid (COL) “Barkhos” have been carried out. The studies were carried out by the methods of nanoindentation, fractography, and X-ray photoelectron spectroscopy. It was found that such coatings have a two-level horizontallayered structure. Проведено дослідження структури і властивостей газофазних покриттів, одержуваних з використанням хромоорганічної рідини (ХОР) «Бархос». Дослідження проводили методами наноіндентування, фрактографії і рентгенівської фотоелектронної спектроскопії. Встановлено, що такі покриття мають дворівневу горизонтально-шарувату структуру. Проведено исследование структуры и свойств газофазных покрытий, получаемых с использованием хромоорганической жидкости (ХОЖ) «Бархос». Исследования проводили методами наноиндентирования, фрактографии и рентгеновской фотоэлектронной спектроскопии. Установлено, что такие покрытия имеют двухуровневую горизонтально-слоистую структуру.